A history of childhood trauma is associated with slower improvement rates: Findings from a one-year follow-up study of patients with a first-episode psychosis. Issue 1 (December 2016) - Aas, Monica; Andreassen, Ole; Aminoff, Sofie; Færden, Ann; Romm, Kristin; Nesvåg, Ragnar; Berg, Akiah; Simonsen, Carmen; Agartz, Ingrid; Melle, Ingrid
Abstract Background The aim of this study was to investigate whether childhood trauma was associated with more severe clinical features in patients with first-episode psychosis, both at the initial assessment and after one year. Methods Ninety-six patients with a first-episode of a DSM-IV diagnosis of psychosis, in addition to 264 healthy controls from the same catchment area, were recruited to the TOP NORMENT study. A history of childhood trauma was obtained using the Childhood Trauma Questionnaire (CTQ). Function and symptom severity were measured using the Global Assessment of Functioning (GAF) Scale divided into function (GAF-F) and symptoms (GAF-S), the Positive and Negative Syndrome Scale (PANSS) and the Young Mania Rating Scale (YMRS). All clinical assessments were completed at two time points: At an initial assessment within the first year of initiating treatment for psychosis and after one year. Results Childhood trauma was associated with significantly reduced global functioning and more severe clinical symptoms at both baseline and follow-up, whereas emotional neglect was associated with a significantly reduced improvement rate for global functioning (GAF-F) over the follow-up period. Conclusion Our data indicate that patients with first-episode psychosis who report a history of childhood trauma constitute a subgroup characterized by more severe clinical features over the first year of treatment, as well as slower improvement rates.